EFFECT OF MINERAL NUTRITION ON THE YIELD OF ON BIOETHANOL FROM SWEET SORGHUM - Мулярчук, О. І.; Кобернюк, О. Т. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The results of studies on the impact of basic fertilizer and foliar plant sweet sorghum in the output of energy and bioethanol. Optimization of the ground and foliar fertilizer plant sweet sorghum in the production of bioethanol. The studies were conducted in the State Agrarian and Engineering University in Podilya during 2013- 2015. The layout of the experience included: 1.Monitoring-without fertilizer; 2. N60P60K60-basic fertilizer; 3. Yarylo -foliar fertilizer at tillering stage rate of 3 l / ha; dissolved in 300 l / ha of water; 4. N60P60K60 autumn + Yarylo in the tillering phase 3 l / ha. The cultivation technology of sweet sorghum has been accepted for the western forest-steppe of Ukraine. The rate of grade Silosnoye 42 by plating with a row spacing of 45 cm. was 200 thousand of seeds / ha. The harvest of green mass sorghum cleaned in the phase of panicle formation and wax ripeness. Macro- and microelements for plant′s life are quite important and can not be replaced by others. The number of necessary plant microelements compared to macro are small; but even a slight deficiency of them can lead to destruction of the plant. So you need to put nutrients by foliar feeding. From mikroelements sorhum is the most sensitive to manganese; zinc; iron; molybdenum; less sensitive to copper; poorly responsive to boron and sulfur. All these elements contain fertilizer Jarylo; it is not toxic and environmentally safe for people.